A Study Of The Effects Of Strategic Management And Policy Innovation On Business Results In China - Yang, Zhang; Abbas Ali, Dhakir (Journal of Neonatal Surgery, 2025)
Researchers in this quantitative study compare the strategic management, policies, and outcomes of several Chinese enterprises. This research will assess the impact of government laws and strategic planning on several performance metrics, such as market share, innovation, profitability, and overall corporate performance in China. Strategic management strategies, including long-term planning, competitive positioning, resource allocation, and the influence of domestic laws and regulations were evaluated by surveying several Chinese firms from diverse industries. Data was analyzed using regression. strong strategic management is substantially associated with strong firm performance, according to the data. Profitability, market share, and operational efficiency are all positively affected by these for firms that regularly use frameworks for strategic management. Additionally, the report shows that regulatory help, trade policies, and government incentives all contribute to a company's performance. The article stresses that for organizations to succeed, their strategies must be in sync with the objectives of national policy. Businesses do better than their competitors whose tactics don't adapt to the ever-changing local markets and regulatory landscape. According to the paper, Chinese businesses may improve their competitiveness in both domestic and global markets by coordinating their strategic planning with official government initiatives. These findings are helpful for foreign companies attempting to understand China's business landscape because they provide light on the effects of managerial and strategic policy decisions on Chinese company performance.